2022
DOI: 10.3390/ijms23158547
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate

Abstract: Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The denaturing effect of Gdm + on DNA origami is furthermore strongly modulated by its counteranion, with Gdm 2 SO 4 and GdmSCN being much weaker and stronger denaturants, respectively. [75,76] This is because these anions themselves are either chaotropic (SCN − ) or kosmotropic (SO 4 2− ) and thus alter the structure of bulk water and especially the hydration shell of DNA, which modulates the heat capacity change of the transition between intact and denatured DNA origami nanostructures. [75] A direct result of this is a nonmonotonous temperature dependence of DNA origami denaturation, that may display local minima and maxima of DNA origami stability at intermediate temperatures.…”
Section: Secondary Ionic Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The denaturing effect of Gdm + on DNA origami is furthermore strongly modulated by its counteranion, with Gdm 2 SO 4 and GdmSCN being much weaker and stronger denaturants, respectively. [75,76] This is because these anions themselves are either chaotropic (SCN − ) or kosmotropic (SO 4 2− ) and thus alter the structure of bulk water and especially the hydration shell of DNA, which modulates the heat capacity change of the transition between intact and denatured DNA origami nanostructures. [75] A direct result of this is a nonmonotonous temperature dependence of DNA origami denaturation, that may display local minima and maxima of DNA origami stability at intermediate temperatures.…”
Section: Secondary Ionic Interactionsmentioning
confidence: 99%
“…[75] A direct result of this is a nonmonotonous temperature dependence of DNA origami denaturation, that may display local minima and maxima of DNA origami stability at intermediate temperatures. [75,76] Many of the observations discussed in this section rely on specific properties of the employed ions, such as the ability of Gdm + to participate both in hydrophobic and electrostatic interactions and to even undergo like-charge ion pairing. [77] Their impact on DNA origami stability in vivo is therefore rather limited.…”
Section: Secondary Ionic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigated the interaction of 2D DNA origami nanostructures with guanidinium (Gdm + ) salts and focused on the effects of different environmental parameters such as Gdm + concentration, 26 temperature, 26 ionic strength, 29 time, 26,28 and counterion species. 27,28 A surprisingly complex picture was revealed that included for instance strong counterion effects, 27,28 non-monotonic temperature dependencies, 27,28 and a counterintuitive destabilizing influence of additional cations. 29 The origin of these observations lies in the structure of the Gdm + cation (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…, the so-called Rothemund triangle. 26–29 However, it is well established that DNA origami stability under various conditions depends on the overall shape as well as certain design choices, e.g. , lattice type and crossover arrangement.…”
Section: Introductionmentioning
confidence: 99%